The Application of a Sliding Mode Observer in a Speed Sensor Fault Tolerant PMSM Drive System - Kamila Jankowska; Viktor Petro; Mateusz Dybkowski; Karol Kyslan (IEEE Access, 2023)
The fault-tolerant control system (FTCS) for a permanent magnet synchronous motor (PMSM) is presented and an analysis of speed sensor faults is proposed in this paper. The detection and compensation of speed sensor faults is based on the simple comparison of the measured signals with the signals estimated by reduced-order sliding mode observer (SMO). The focus of the work is on the presentation of simulation and experimental research for the most common speed sensor failure types: complete signal loss, gain error, and measurement noise. Additionally, an analysis of different operating conditions of the PMSM drive system is presented, which highlights the system’s behaviour under various conditions. The presented algorithm enables the fast detection and compensation of failures with very short detection times, making it a versatile solution for a PMSM drive system and improving its overall reliability.